(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article identifies that psychological readiness for marriage is a complex personal formation, with its main components being: marital values, marriage motivation, the concept of marital hierarchy, marital relationships and expectations, and the idea of marital relations. It was determined that each component has its own structural composition.